2013
DOI: 10.1371/journal.pone.0062001
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of CD8 Delays Reendothelialization and Accelerates Neointima Formation in Injured Arteries of Mouse via TNF-α Inhibiting the Endothelial Cells Migration

Abstract: ObjectiveDelayed or impaired reendothelialization is a major cause of stent thrombosis in the interventional treatment of coronary heart disease. T cells are involved in neointima formation of injured arteries. However, the regulated mechanism of reendothelialization and the role of CD8 T cell in reendothelialization are unclear.Methods and ResultsImmunofluorescence staining showed that CD8 positive cells were increased in wire injured femoral artery of mice. On day 21 after injury, elastin staining showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Identification of possible CD8 T cell interactions with injured vascular wall, while novel in humans, is in line with studies showing the importance of CD8+T cells in the vascular injury response in mice [30, 31]. Interestingly, CD8 knockout increased neointimal formation and TNF levels in injured arteries and was also associated with delayed re-endothelialization [31]. The effect of CD8+ T cells on reduced neointima formation after arterial injury was attributed in part to increased function of the CD28high phenotype.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Identification of possible CD8 T cell interactions with injured vascular wall, while novel in humans, is in line with studies showing the importance of CD8+T cells in the vascular injury response in mice [30, 31]. Interestingly, CD8 knockout increased neointimal formation and TNF levels in injured arteries and was also associated with delayed re-endothelialization [31]. The effect of CD8+ T cells on reduced neointima formation after arterial injury was attributed in part to increased function of the CD28high phenotype.…”
Section: Discussionsupporting
confidence: 69%
“…These changes were absent in sham sampling procedures and were not observed in other cell populations. Identification of possible CD8 T cell interactions with injured vascular wall, while novel in humans, is in line with studies showing the importance of CD8+T cells in the vascular injury response in mice [30, 31]. Interestingly, CD8 knockout increased neointimal formation and TNF levels in injured arteries and was also associated with delayed re-endothelialization [31].…”
Section: Discussionmentioning
confidence: 52%
“…The vessel tissue processing method was conducted and the degree of neointima formation was evaluated by measuring the luminal cross-sectional areas ( 23 , 24 ).…”
Section: Methodsmentioning
confidence: 99%
“…Research indicates that T cells are associated with exacerbation of atherosclerotic lesions, 19-21 while showing a protective effect against NIH after arterial injury. 22, 23 Interestingly, in the setting of arterial injury, further characterization revealed that this protective effect was mediated by CD8 + cells, 24-26 while their CD4 + counterparts in fact promoted neointima development. 27 …”
Section: Introductionmentioning
confidence: 99%